SINDROME BENIGNO DE HIPERMOVILIDAD ARTICULAR: ESTUDIO CLINICO - Vidal N., Luis (2024)
In the present paper, we studied the prevalence, clinical an caracteristics ofthe benign hypermotility syndrome in 575 healthy volunteers. Tite diagnosis was established using tbe Carter and Wilkinson criteria with the modification of Deighton. The global prevalence ofthe benign hypermotility syndrome in our population was 17.21 %. The prevalence clearly locrense with the age and was higher in women (21.65%) titan in men (11.87%). We found a stntistical significative association (p< 0.05) between the benign hypermotility syndrome and the development of osteartrosic cl1anges. We discuss the sensibility and specificity or the diagnostic criterias.